2022
DOI: 10.3389/fcell.2022.817402
|View full text |Cite
|
Sign up to set email alerts
|

Monocytic Myeloid-Derived Suppressor Cells Inhibit Myofibroblastic Differentiation in Mesenchymal Stem Cells Through IL-15 Secretion

Abstract: Background: Accumulating evidence indicates that mesenchymal stem cells (MSCs) are precursors of myofibroblasts, which play a vital role in renal fibrosis. The close interaction between MSCs and other immune cells regulates the development of multiple fibrosis-related diseases. However, the effect of myeloid-derived suppressor cells (MDSCs) on MSCs remains unexplored. Here, we investigated the effect of MDSCs on the myofibroblastic differentiation of MSCs.Methods: MSCs were induced to undergo myofibroblastic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Similarly, BMMSCs were also used to treat brotic diseases, such as idiopathic pulmonary brosis, non-alcoholic fatty liver brosis, skin brosis and so on, due to the immunomodulatory function of BMMSCs to the recipient cells [34][35][36]. However, in recent years, researchers found that BMMSCs could differentiate into myo broblasts which is the key effector cell in brosis, in particular microenvironment including irradiation injury [37,38]. This brogenic differentiation phenomenon makes MSCs a potential danger to aggravate brosis stimulated by irradiation or other factors [39].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, BMMSCs were also used to treat brotic diseases, such as idiopathic pulmonary brosis, non-alcoholic fatty liver brosis, skin brosis and so on, due to the immunomodulatory function of BMMSCs to the recipient cells [34][35][36]. However, in recent years, researchers found that BMMSCs could differentiate into myo broblasts which is the key effector cell in brosis, in particular microenvironment including irradiation injury [37,38]. This brogenic differentiation phenomenon makes MSCs a potential danger to aggravate brosis stimulated by irradiation or other factors [39].…”
Section: Discussionmentioning
confidence: 99%
“…The renal fibrosis model and MSC therapy scenario were utilized according to the previous studies [ 21 , 22 ]. C57BL/6 mice were divided into the following groups.…”
Section: Methodsmentioning
confidence: 99%